Synthesis and characterization of Fe(III)-doped ceramic membranes of titanium dioxide and its application in photoelectrocatalysis of a textile dye - Rodrigues, Emanuel C.; Soares, Layciane. A.; Modenes Jr, Marco A.; Sene, Jeosadaque J.; Bannach, Gilbert [UNESP]; Carvalho, Claudio T. [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 2011)
Foram preparadas suspensões de TiO2 dopadas com Fe(III) pelo método sol-gel. As propriedades dos materiais dopados foram comparadas com a de TiO2 puro, baseadas na caracterização por análise térmica (TG-DTA e DSC), difratometria de raios X e medidas espectroscópicas (FTIR). As suspensões de TiO2 puras e dopadas foram depositadas sobre substrato metálico, obtendo-se assim eletrodos de filme fino. O tratamento térmico destes precursors a 400 ºC por um período de 2 horas resultou na formação de fase cristalina anatase. Os eletrodos foram utilizados em processo fotoeletrocatalítico para a degradação de corante têxtil em solução aquosa. Verificou-se que o eletrodo de TiO2 puro apresentou melhor desempenho no processo de degradação do corante.

Pure and Fe(III)-doped TiO2 suspensions were prepared by the sol gel method with the use of titanium isopropoxide (Ti(OPri)4) as precursor material. The properties of doped materials were compared to TiO2 properties based on the characterization by thermal analysis (TG-DTA and DSC), X-ray powder diffractometry and spectroscopy measurements (FTIR). Both undoped and doped TiO2 suspensions were used to coat metallic substrate as a mean to make thin-film electrodes. Thermal treatment of the precursors at 400ºC for 2 h in air resulted in the formation of nanocrystalline anatase TiO2. The thin-film electrodes were tested with respect to their photocatalytic performance for degradation of a textile dye in aqueous solution. The plain TiO2 remains as the best catalyst at the conditions used in this report.
Síntese e caracterização de membranas cerâmicas de dióxido de titânio dopadas com Fe(III) e sua aplicação em fotoeletrocatálise de corante têxtil
Keywords: TiO2; dopagem; caracterização; eletrodos de filme fino; corante têxtil; TiO2; Fe(III) doping; characterization; thin film electrode; textile dye